A utilização da terceirização como fator de (in)eficiência de serviços públicos na Universidade Federal do Espírito Santo, campus São Mateus - Pereira, Diego Jordem (2023)
The provision of public services is an essential note in a democratic State that seeks to preserve a model of equity and guarantee services to all citizens on a regular and continuous basis. And public-private collaboration resources have been a constant to make the guarantee of these services effective. In particular, in this context, outsourcing is evident, with many arguments being invoked to justify the viability of its implementation. Governments around the world outsource public services in the name of efficiency and increased service quality, however, there is little evidence to support this information. The problem is that the indirect provision of public services in collaboration with the private sector is not always more economical or efficient, on the other hand, not all services are more efficient and sustainable with direct provision. It cannot be forgotten that the primary objective in the provision of public services must be the best provision of the service, regardless of how it is provided by the State, whether directly or indirectly. This question should always be essential in this debate, so what elements should guide the outsourcing of public services? Thus, as a main objective, it was proposed to point out whether the execution of outsourced services at the Federal University of Espirito Santo, São Mateus campus, is efficient and with quality that serves the academic community. The theoretical contribution focused on the Outsourcing of Public Services, efficiency and public principles, as well as other principles of Public Administration. For the study of the research problem, the methodological procedure used was the systematic review in the first part of the study, by jurisprudential studies and scientific productions; the documentary analysis, in the second part of the study, using preexisting documentary sources, available on the federal transparency portal, as well as by the Federal University of Espírito Santo; and the descriptive analysis, used in the analysis of the results of the questionnaires and comparisons/combinations with the results obtained in the second stage (document analysis), thus describing the characteristics of the target population of the research, as well as establishing relationships between the variables. As a result, it was shown that there is a significant negative relationship between expectations and the performance of the service quality of outsourced companies at the Federal University of Espírito Santo, São Mateus campus. This time, it is concluded that the outsourced services provided do not meet the expectations of the academic community. From the results, as a technological product, a booklet was elaborated containing guidelines and information on the outsourcing of public services, to be made available to the Managers of the Federal University of Espirito Santo.